FINANCIAL LITERACY INFLUENCING FACTOR ANALYSIS TO STUDENTS IN BATAM CITY - Lita Christina; Felycia Fernanda Wijaya (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Over time and the instability of economic conditions, financial literacy is an important factor influencing the recovery of these conditions. Therefore, this study aims to determine the factors that affect financial literacy. This study uses a multiple linear regression model with a sample size of 402 which was tested through the SPSS application. The results showed that money attitude, financial knowledge, and financial behavior had a significant effect on financial literacy. Meanwhile, the other three variables, namely financial education, financial socialization agents, and financial attitude do not have a significant effect on financial literacy